Effect of inactive volume on thermocouple measurements of electrocaloric temperature change in multilayer capacitors of 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3. (22nd September 2017) - Usui, T; Hirose, S; Ando, A; Crossley, S; Nair, B; Moya, X; Mathur, N D
Abstract: On increasing the active/total volume ratio of 0.9Pb(Mg1/3 Nb2/3 )O3 –0.1PbTiO3 multilayer capacitors (MLCs), the electrocaloric temperature change measured using a thermocouple near the centre increases, until saturating to reveal the nominally adiabatic limit (|Δ T | ~ 2.7 K for rapid field changes of |Δ E |  =  28.8 V µ m −1 ). For all MLCs that we studied, the practice of multiplying the measured temperature change by the total/active heat capacity ratio causes the adiabatic temperature change to be overestimated by a small numerical factor. These findings highlight the challenge associated with quantifying electrocaloric effects in MLCs of the type that are currently being used as working bodies in prototype cooling devices.